Cracking susceptibility of sour cherry (Prunus cerasus L.) in Hungary and relation to calcium application - Simon, G.; Tóth, M.; Papp, J. (International Journal of Horticultural Science, 2007)
The rain induced fruit cracking is a big, serious problem especially for sour cherry growers but in some year sour cherry growers had also problem with fruit cracking caused by too much rainfall in the harvesting season. The cracked sour cherry fruits can be easily infected by different diseases like Monillinia sp. Cracked and infected fruits can not be transported for long distance and using for preservation because they lost their market value by the pour fruit quality. There are two possibilities to protect fruits against the rain induced fruit cracking. The most effective protection technique is the plastic rain cover over the tree rows. The installation of these equipments is too expensive for the growers. That is the reason why researchers tried to find other less expensive and sufficiently effective ways like sprayings different mineral salts, hormone and other type chemicals against the rain induced fruit cracking. Several calcium formulas calcium chloride (CaC12), calcium hydroxide (Ca (OH),) and calcium nitrate (Ca(NO3)2) can be sprayed in appropriate solution concentration. The aim of our trial is to determinate the fruit cracking susceptibility of wide grown Hungarian sour cherry varieties and find the most effective calcium formula and its concentration for spraying in orchards to prevent the fruit cracking. In the first trial year (2006) cracking index of tested sour cherry varieties were determined under field and laboratory conditions. Under field conditions were not found differences between cracking tendency of tested cultivars. After results of immersing fruits in distillated water for 24 hours tested sour cherry varieties were divided to three groups by the susceptibility to rain induced fruit cracking: very susceptible (`Maliga emléke’, ’Piramis’, ’Érdi jubileum’, ’Erdi nagygyümölcsű’ and ’Meteor korai’); susceptible ‘Érdi bőtermő, Tandy 279’ and Cigány 59.; moderately susceptible/tolerant ("T" and "R" clones). In the second trial year (2007) calcium chloride (CaCl2) and calcium nitrate (Ca(NO3)2) were sprayed in 0,35m/m%; 0,5m/m% and 1,0m/m% solution concentration. One more commercial product "Damisol-Kalcium" was also applied in the advised 1,0m/m% concentration. Like in the trial year before (2006) under field conditions we did not kept differences between the cracking susceptibility of varieties and calcium treatments. As the result of laboratory testing (immersing calcium treated fruits in distillated water) we kept that calcium chloride (CaCl2) seems the most effective against the fruit cracking in 0,5m/in% solution concentration. The other calcium formulas also decreased the cracking ratio but in less scale.